Pre-cooling improves cycling performance in hot/humid conditions - Smith, J. A.; Yates, K.; Lee, H.; Thompson, M. W.; Holcombe, B. V.; Martin, D. T. (Medicine & Science in Sports & Exercise, 1997)
Whether pre-cooling of the torso skin prior to competition would delay onset of fatigue was examined in male (N = 9) triathletes. A cooling vest produced a skin temperature of 10 degrees Celsius compared with 33 degrees when no vest was worn. Onset of fatigue was delayed in the pre-cooled condition. The slower onset of fatigue may be due to less blood being diverted to the skin during exercise. Implication. Pre-cooling the skin to temperatures much colder than ambient surroundings delays the onset of fatigue.